TRENDS IN THE DEVELOPMENT OF LOCAL SELF-GOVERNMENT IN MOSCOW - N. Musinova (Вестник университета)
The state status of Moscow city requires the solution of the question of the correlation of opportunities and powers of the city authorities and the lower level of territorial management of the city, based on the need to preserve the unity of the urban economy. From this perspective, the stages of development of local self-government in Moscow are considered. Attention to the nature of the organizational changes at the local level, which began with the accession of new territories to Moscow in July 2012, - is focused. Transformation of the organization of state and municipal management of the city is analyzed, tendencies of development of local government in the city of Moscow are defined.